Prevalence of Hepatitis B and C Infection Among Street Children Community in Malang City - Syifa Mustika; Charisma Dian Simatupang (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: World Health Organization (WHO) announced that during 2017, 325 million people worldwide were infected with the hepatitis B virus (HBV) or hepatitis C virus (HCV). Street children community is a part of society that is susceptible to HBV and HCV transmission, yet no data available about the prevalence. The purpose of this study was to determine the prevalence of hepatitis B and hepatitis C infections in street children community of Malang during 2017.Method: This cross-sectional study was conducted in September 2017 with subjects of street children who were members of the East Java Humanitarian Network (EJHN) group. They were interviewed, got vital signs examined, and performed HBsAg and anti HCV tests using the ECLIA method.Results: There were 90 subjects, with more male than female (60%). The most frequent age range was between 21 to 30 years (35.6%). Most of them do not have permanent jobs (37.8%). The level of education varied, with 30% were at the level of primary education and 56.7% were married. There were 4.4% hepatitis B positive and 1.1% of hepatitis C positive among the subjects. Subjects with positive results had history of free sex, tattoos, and intravenous drugs abuse as the risk factors of HBV and HCV transmission.Conclusion: The prevalence of Hepatitis B and Hepatitis C in the population of street children in Malang city, East Java, were 1.1% and 4.4%, respectively. The most common risk factors were free sex and tattoos.